Inclusion and Exclusion of Social Actors in Judi Online ‘Online Gambling’ News:A Corpus-Assisted Critical Discourse Analysis Approach on Kompas.com - Budiawan, Raden Yusuf Sidiq; Mualafina, Rawinda Fitrotul; Siti Ulfiyani; Mukhlis (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Abstract. This study aims to describe the inclusion and exclusion of social actors in online gambling news coverage on Kompas.com using a critical discourse analysis approach assisted by corpora. By utilizing this approach, the language patterns used in the coverage are systematically analyzed to explore how the issue of online gambling is framed by the media. The findings reveal that the coverage predominantly features the government, such as